Inovasi Produk Rumah Tangga: Pelatihan Sabun Cuci Piring bagi Masyarakat Desa Sugihen, Juhar, Karo - Habibah Salsabila Addary; Siti Aisyah; Fadli Endi Tama; Fahira Rahmah Hani; Mulia A Sura (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Community Service Learning (CSL) is a tangible manifestation of the implementation of the Tri Dharma of Higher Education, which aims to apply knowledge within the community, particularly in addressing economic challenges in rural areas. This study focuses on the effectiveness of the UIN SU student KKN programme in Sugihen Village, Juhar Subdistrict, Karo Regency, which carries the theme of economic empowerment of the community. The research method used a qualitative approach with participatory observation and practical demonstration techniques, directly involving the Sugihen Village community. The results showed that this programme significantly improved the participants’ knowledge and technical skills, transforming their roles from passive consumers to active producers. This training not only helped reduce household expenses but also opened up new business opportunities that had the potential to increase family income. Therefore, this KKN programme can serve as an effective strategic model for creating stable and independent community-based economic growth.